Editorial: Coral reef restoration in a changing world: science-based solutions - Arias - González, Jesús E. (2022)
Coral reef ecosystems are impacted globally by anthropogenic and climate change, altering ecosystem functioning, and the goods and services reefs provide to societies (Bindoff et al., 2019). Further deterioration of the reef framework and decreases in reef-associated biodiversity are expected, necessitating rehabilitation responses. With the increase of anthropogenic impacts, scientists, conservationists, environmentalists, and decision-making authorities initially employed traditional conservation and rehabilitation approaches (such as additional marine protected areas, no use zones, etc.), and practices that aimed to reduce local stressors such as fisheries and tourism, following the rationale that these activities will lead to rehabilitation of reefs by natural recovery. Yet, this approach of ‘passive restoration’ has generally failed to achieve its goals (Rinkevich, 2008). As a result, more and more practitioners and scientists are opting for active reef restoration (Baums et al., 2019; Bindoff et al., 2019; Bayraktarov et al., 2020; Kleypas et al., 2021), where human activities directly foster the recovery of damaged reef ecosystems. Advances in fundamental science, further development of an applied tool-box (Vardi et al., 2021), and supplementary ecological engineering approaches (Rinkevich, 2021) are needed to help active restoration succeed. In one way, the declaration of the Decade on Ecosystem Restoration by the United Nations has raised interest in the methods needed to implement best practices for maximum gain. In another way, the International Coral Reef Society (ICRS) has recently published a science to policy paper (Knowlton et al., 2021) describing a “plan to save coral reefs” where three main pillars are presented as equally important for corals to be retained: 1) mitigation of CO2 emissions; 2) mitigation of local pollution; and 3) active restoration. Our most important scientific society pointed out active restoration as one of the requirements for coral reefs to “survive”. Yet a lack of restoration protocols, clear criteria for restoration outcomes and financial support posed significant obstacles to its maturation. Based on the above, this Research Topic entitled: ‘Coral Reef Restoration in a Changing World: Science-based Solutions’ aimed, to encourage and collect studies searching for innovative techniques and ecological engineering approaches in coral reef restoration programs, with an eye to current and anticipated stressors that affect coral reef ecosystems. [...]